Characteristics of female sexual dysfunctions and obstetric complications related to female genital mutilation in Omdurman maternity hospital, Sudan - Khalid Yassin (Reproductive Health, 2018)
Abstract Background Female genital mutilation (FGM) is a major public health problem, especially in developing countries. Method This was a prospective observational cohort study conducted over six months duration (1st July-31st December 2015) at Omdurman Maternity Hospital, Khartoum, Sudan, primarily to determine whether exposure to FGM/C (exposed Vs. non-exposed) and degree of exposure (type III Vs. type I) are associated with impaired sexual function or not?. As secondary objective, the study also investigated the association between FGM/C and postpartum complications (eg: difficulties in cervical examination, episiotomy wound infection, postpartum bleeding) by following the participants from the time of admission at the hospital, through vaginal delivery and until the 6th post-partum week. Results A total of 230 (subjected to FGM/C) and 190 (not subjected to FGM/C) women were approached. The clinical examinations evidenced that the majority (67.8%) had FGM type 3, while the remainder (32.2%) had type 1. The most common reported sexual complication was dyspareunia (76%). Bleeding following first attempt of sexual intercourse was reported in 35.2% followed by reduced sexual desire 62.6%, reduced sexual satisfaction 40.9% and need for surgery to release labial adhesions at first attempt of sexual intercourse 30.4%. With regard to FGM- related complications that occurred during labor 76.5% required an episiotomy, 61.7% experienced difficulties in cervical examination, 57.8% needed defibulations during second stage of labor, 26.5% complicated by episiotomy wound infection and 2.2% developed obstetric hemorrhage. In this study FGM/C was a significant factor increasing the risk of sexual complications. Interestingly when using logistic regression analysis the FGM-related complications were not significantly varied by FGM/C types. Conclusion Our observations indicate that FGM/C is a serious public health problem and there should be an urgent intervention such as planned health education campaigns to end FGM/C practice.